Research on the failure behavior of cement- and fiber-reinforced sand under triaxial tensile loads - Ahmeti, Hysen; Behrami, Ragip (Oficyna Wydawnicza Politechniki Wrocławskiej, 2025)
The primary objective of this research is to investigate the failure behavior of sand treated with cement and fibers under triaxial tensile loading conditions. To achieve this, a new loading system and triaxial cell were developed for conducting tensile tests. The specimens included sand samples with 3 and 5% cement content (dry weight) and two types of polypropylene fibers with a length of 24 mm and diameters of 23 and 300 μm, incorporated at dosages of 0.0 and 0.5% (dry weight) of the sand–cement mixture. After a curing period of 7 days, the specimens were tested under direct triaxial tension at confining pressures of 100, 200, and 300 kPa under drained conditions. The stress–strain behavior, volumetric changes, and energy absorbed by the cement- and fiber-reinforced sand were analyzed and compared with data from other studies. The results showed that the addition of fibers led to a reduction in the peak deviator stress and an increase in the residual deviator stress of the cement- and fiber-reinforced sand, indicating a transition from brittle to ductile behavior. Additionally, a decrease in initial stiffness and stiffness at 50% of the maximum tensile stress was observed with the incorporation of fibers, with the effect becoming more pronounced as the fiber diameter increased. The energy absorbed by fibers with a diameter of 23 μm was lower compared to those with a diameter of 300 μm. The addition of fibers also influenced the strength parameters, resulting in a decrease in the cohesion intercept and an increase in the internal friction angle.
Studia Geotechnica et Mechanica, Vol. 47, 2025, nr 3, s. 27-45
Poprzedni tytuł: Studia Geotechnica
Keywords: geotechnika - czasopisma; mechanika - czasopisma; sand; cement; triaxial loading; fibers